Analysis of serum hepatitis B virus RNA levels among HBsAg and HBsAb copositive patients and its correlation with HBV DNA. Issue 40 (8th October 2021) - Xiang, Yu; Yang, Yang; Chen, Pu; Lai, Xiaofei; Shi, Shan; Li, Shuang; You, Wenxian
Abstract : Abstract: There are approximately 2 billion HBV-infected individuals worldwide, and approximately 1.87% to 7% of these individuals are copositive for HBsAg and HBsAb. Our study detected hepatitis B virus pgRNA (HBV RNA) levels in HBsAg and HBsAb copositive patients and then analyzed the correlation with HBV DNA, HBsAg, ALT, and AST levels. A total of 149 HBsAg and HBsAb copositive patients were identified from 66, 617 outpatients. HBV RNA, HBV DNA, HBsAg, ALT, and AST serum levels were significantly different in different natural phases of HBV infection (immune tolerance phase, immune clearance phase, low replication phase, and reactivation phase) with statistical significance ( P < .01). HBV RNA levels were positively correlated with HBV DNA, HBsAg, ALT, and AST levels. HBV RNA and HBV DNA levels were significantly increased in the HBeAg-positive group (66 patients) compared with the HBeAg-negative group (83 patients) ( P < .01). In the HBeAg-positive group, HBV RNA levels were positively correlated with HBV DNA and HBsAg levels. In the HBeAg-negative group, HBV RNA levels were positively correlated with HBV DNA. Serum HBV RNA levels were positively correlated with HBV DNA, HBsAg, ALT, and AST levels. HBV RNA could be used as a virological indicator for antiviral therapy in HBsAg and HBsAb copositive hepatitis B patients.